Kemiskinan Global Dalam Prespektif Development as Freedom Amartya Sen Kasus: Indonesia - Indro, P.Y. Nur (Jurnal Ilmiah HUBUNGAN INTERNASIONAL, 2013)
On poverty reduction is the ultimate goal of human development globally. Amartya Sen offers a perspective known as Development as Freedom, which prioritizes freedom as a goal and instrument development. Categories of development success, especially in humans as subjects who have an ever increasing freedom.Keywords : freedom, development, poverty, autonomy of human